A new experimental method to separate interfacial and internal mass transfer on coated adsorbent. (August 2019) - Seol, Sung-Hoon; Nagano, Katsunori; Togawa, Junya
Highlights: The interfacial mass transfers was obtained by using thin coated samples (27–79 μm). Average error between experimental and calculated K m was in acceptable range (±14%). Proper coating thickness is 0.8 mm and 1.0 mm for WSS composite and A-type silica gel. Abstract: This study presents a simple and reasonable experimental methodology for separating the effects of interfacial and internal mass transfers from an overall mass transfer. First, the mass transfer in the range of thickness with negligible internal mass transfer resistance is experimentally observed. It was assumed that the effect of the internal mass transfer can be neglected if the sorption dynamic data of two thin-coated samples correspond with each other. Then, the internal mass transfer resistance is calculated by subtracting the interfacial mass transfer resistance from the overall resistance. The adsorbent, named Wakkanai Siliceous Shale (WSS) impregnated with lithium chloride of 20 wt%, was coated on sample plates with different thicknesses (27 μm, 65 μm, 0.19 mm, 0.38 mm and 0.71 mm). The large pressure jump (LPJ) method was used, and adsorption dynamic characteristics were gravimetrically measured. Based on the experimental data, the adsorption dynamics of composite WSS-coated layers were compared with those of the layers coated by an A-type silica gel to verify the applicability of a composite adsorbent using WSS on adsorption heat pump systems.